ANALISIS PEMBERIAN KREDIT PADA USAHA EKONOMI KELURAHAN SIMPAN PINJAM (UEK-SP) DI KELURAHAN SIMPANG TIGA KECAMATAN BUKIT RAYA KOTA PEKANBARU - Elma Gusti; Mariaty Ibrahim (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
This research was conducted at the Simpang Tiga Urban Village Business Savings and Loans (UEK-SP) office. PPD (Village Empowerment Program) is one of the non-bank financial institutions created by the government to encourage the economic development of the Village / Kelurahan community through micro economic activities through the Village / Kelurahan Business Fund managed by UEK-SP (Villange Savings and Loan Economic Business). UEK-SP is a village institution engaged in savings and loans to support productive economic businesses in the village concerned. The purpose of this study is to find out how the procedure for granting credit is carried out by UEK-SP Simpang Tiga in granting credit to its customers. Data collection techniques that the authors use in this study are observation and interview techniques. The results of the research show that the procedure used in the UEK-SP Simpang Tiga in granting credit is (Credit Provision Process, Credit Granting Decision, Credit Granting Analysis) Has been carried out by the UEK-SP Simpang Tiga as it should in the credit granting procedure and this makes the business the government in empowering the community can be achieved.  Keywords: crediting process, application for credit, crediting analysis, disbursement and credit monitoring.